The strategy-focused organization : how balanced scorecard companies thrive in the new business environment - Kaplan, Robert S.; Norton, David P. (Boston, Mass. : Harvard Business School Press, 2001)
Presenting a practical, proven framework steeped in rich case study experience, The Strategy-Focused Organization helps solve a universal management problem - not just how to formulate strategy, but how to make it work. Building on one of the most revolutionary business ideas of our time, this important book shows how today's leaders can shape their own companies to meet the challenges and reap the rewards of a new competitive era.
Includes bibliographical references and index.
rua 21/05/13
Loans
Keywords: Strategic planning; Balanced scorecard